2017
DOI: 10.1016/j.jmapro.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of local surface texture by tool impression on the self-piercing riveting process and the static lap shear strength

Abstract: To increase fuel efficiency and reduce emission, aluminium alloys have been increasingly used in automotive body-in-white structures for lightweighting. Due to its advantages over some of the more traditional joining technologies, self-piercing riveting (SPR) has been widely used for these lightweight structures. Research has showed that friction is a very important factor that influences both the riveting process and joint strength for SPR, but these influences have not been fully understood. In this paper, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…They confirmed that the SPR joints with material of higher surface friction had higher static lap shear strength. Further research from Li et al [13] confirmed that the critical location of friction influence on lap shear strength was between the top and bottom sheet around the tip of the punched hole in the top sheet.By studying the influence of local pin impression with garnet particles (with different ring sizes around the rivet piercing location) on static lap shear strength of SPR joints,they proved that the impression with the smallest ring and garnet particles (right around the tip of the punched hole in the top sheet) increased the lap shear strength the most and the strength increase could be up to 16%.…”
Section: Static Strengthmentioning
confidence: 92%
“…They confirmed that the SPR joints with material of higher surface friction had higher static lap shear strength. Further research from Li et al [13] confirmed that the critical location of friction influence on lap shear strength was between the top and bottom sheet around the tip of the punched hole in the top sheet.By studying the influence of local pin impression with garnet particles (with different ring sizes around the rivet piercing location) on static lap shear strength of SPR joints,they proved that the impression with the smallest ring and garnet particles (right around the tip of the punched hole in the top sheet) increased the lap shear strength the most and the strength increase could be up to 16%.…”
Section: Static Strengthmentioning
confidence: 92%
“…It was found that the local surface modification only slightly changed the magnitudes of joint quality indicators. The same author [12] further modified the contact interface conditions between sheets using hot water washing (around 60 • C), P120 sandpaper grinding and grit blasting. The results revealed that the hot water wash and sandpaper grinding did not show a significant influence on the joint quality.…”
Section: Clampingmentioning
confidence: 99%
“…Some efforts have been made to experimentally investigate the effects of surface conditions on SPR joint quality. Surface modification methods, including coating [11], polishing, grit blasting [10], impression [12] and lubricants [13], were adopted by researchers to change the surface conditions. By altering the bottom surface texture of the top sheet with different impression tools and garnet particles, Li [10] explored the influences of the interface condition between two AA5754 sheets on SPR joint quality.…”
Section: Introductionmentioning
confidence: 99%